2006
DOI: 10.1079/phn2005895
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of vitamin B6and concentration of vitamin B6in blood samples of German vegans

Abstract: Objective: The study aimed to evaluate the dietary vitamin B 6 intake and determine the vitamin B 6 concentration in blood samples of German vegans. Design and setting: Cross-sectional study with 33 examination sites all over Germany. Subjects: Ninety-three vegans (50 females) with a mean (^standard deviation (SD)) age of 43.7^15.7 years who took no vitamin supplements. Methods: Dietary intake was assed using a semi-quantitative food-frequency questionnaire. Erythrocyte aspartate aminotransferase activity coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…An investigation of vegans showed a high percentage of marginal to low vitamin B6 status (EAST-AC) despite high vitamin B6 intakes (approx. 2.8 mg/day), and strict vegans were more affected than moderate vegans (242). …”
Section: Demographics and Lifestylementioning
confidence: 90%
“…An investigation of vegans showed a high percentage of marginal to low vitamin B6 status (EAST-AC) despite high vitamin B6 intakes (approx. 2.8 mg/day), and strict vegans were more affected than moderate vegans (242). …”
Section: Demographics and Lifestylementioning
confidence: 90%
“…Total protein intake in vegan groups was the lowest compared to other diet groups (Table 3) [5,12,57]. TEI from protein was approximately 13e15% [5,26,27,31,48,53,57,59,62,63]. WHO recommends protein intake 15% of TEI, dependent on factors such as sex, age, activity, health condition etc.…”
Section: Proteinsmentioning
confidence: 98%
“…Low alcohol consumption is recorded frequently in vegan diets (Table 6) [5,6,10,25,27,28,32,39,44,46e48,53,54,57e59]. However, in some studies, differences in alcohol consumption between diet groups were not observed [12,31,50,63]. Alcohol intake among vegans ranged from 0.25 g/d to 12.6 g/ d [5,6,25,26,32,39,44,46,47,53,54,59,63,68], and in one study [27] as high as 20 g/d for a minority of mainly male vegans.…”
Section: Alcoholmentioning
confidence: 99%
“…Although a large number of studies on vegetarian [24,25,26,27,28,29,30,31,32,33,34,35] and vegan nutrition [20,21,36,37,38,39,40,41] have been published during the last years, only one small study has examined the effect of vegan diets on acid-base homeostasis [42]. Whereas the effect of diets on human acid-base status has significant implications on skeletal health [7,8,9,10,43,44], the primary aim of this cross-sectional study was to investigate how vegan diets affect acid-base balance.…”
Section: Introductionmentioning
confidence: 99%